2014
DOI: 10.1590/s0100-204x2014000300005
|View full text |Cite
|
Sign up to set email alerts
|

Mass and energy balance of the carbonization of babassu nutshell as affected by temperature

Abstract: -The objective of this work was to evaluate the carbonization yield of babassu nutshell as affected by final temperature, as well as the energy losses involved in the process. Three layers constituting the babassu nut, that is, the epicarp, mesocarp and endocarp, were used together. The material was carbonized, considering the following final temperatures: 450, 550, 650, 750, and 850°C. The following were evaluated: energy and charcoal yields, pyroligneous liquid, non-condensable gases, and fixed carbon. The u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
8

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 19 publications
1
7
0
8
Order By: Relevance
“…This value is similar to that obtained for the carbonization of babassunutshell25.8% [32] and shows the potential of fixed carbon production through the slow pyrolysis of babassu nut residues. The pyrolysis conditions are an important role in the development of the rudimentary pore structure in the biochar, through the release of volatiles from the carbon matrix.…”
Section: Yield Of Babassu Endocarp Biocharsupporting
confidence: 86%
“…This value is similar to that obtained for the carbonization of babassunutshell25.8% [32] and shows the potential of fixed carbon production through the slow pyrolysis of babassu nut residues. The pyrolysis conditions are an important role in the development of the rudimentary pore structure in the biochar, through the release of volatiles from the carbon matrix.…”
Section: Yield Of Babassu Endocarp Biocharsupporting
confidence: 86%
“…The babassu residues can contribute significantly to bioenergy production, and the results presented leads to the important economic development, adding value to this product. 63 In their other work, Protásio et al 136 evaluated the carbonization yield of babassu nutshell and the influence of the final temperatures on the energy losses involved in this process. The carbonization process was carried out in an electric oven with a water-cooled condenser and a collection vessel for vapors (pyroligneous liquid).…”
Section: Pyrolysismentioning
confidence: 99%
“…It was concluded that the babassu nutshell is appropriate for charcoal production. 136 For Vinhal et al 137 the study of the babassu palm fruits has great economic importance. The authors observed that almond oil can be used as a fuel in biodiesel production, and in the food and cosmetics industries, as well as other parts of this fruit.…”
Section: Pyrolysismentioning
confidence: 99%
“…Therefore, studies on the use of alternatives biomass, for example, the babassu nut waste, have great potential to be used for energy generation (PROTÁSIO et al, 2014a(PROTÁSIO et al, , 2014b(PROTÁSIO et al, , 2014cREIS et al, 2015). Babassu nutshell showed a high basic density and a suitable lignin content for the sustainable production of bioenergy and charcoal (PROTÁSIO et al, 2014a).…”
Section: Introductionmentioning
confidence: 99%